Questions on algebraic varieties lectures given at a summer school of the Centro Internazionale Matematico Estivo (C.I.M.E.) held in Varenna (Como), Italy, September 7-17, 1969 - C.I.M.E. Summer School Varenna, Italy (969; Marchionna, E. (Ermanno) (Heidelberg, Germany Springer Berlin, 2011)
Dolbeault: Résidus et courants.- D. Mumford: Varieties defined by quadratic equations.- A. Néron: Hauteurs et théorie des intersections.- A. Seidenberg: Report on analytic product.- C.S. Seshadri: Moduli of p-vector bundles over an algebraic curve.- O. Zariski: Contributions to the problem of equi-singula
P. Dolbeault: Résidus et courants -- D. Mumford: Varieties defined by quadratic equations -- A. Néron: Hauteurs et théorie des intersections -- A. Seidenberg: Report on analytic product -- C.S. Seshadri: Moduli of p-vector bundles over an algebraic curve -- O. Zariski: Contributions to the problem of equi-singularit
Originally published: Florence: Cremonese, 1969
Keywords: Algebraic varieties